2020
DOI: 10.5812/ijem.97205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation in Patients with Nonalcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis

Abstract: Context: Vitamin D (VD) has been found to play a key role in nonalcoholic fatty liver disease (NAFLD). This meta-analysis explored the effects of VD supplementation in patients with NAFLD. Methods: The PubMed, EMBASE, and the Cochrane Library databases were searched to find randomized control trials (RCTs) that measured the changes between the VD supplement group and the control group until May 2019. Standard mean difference (SMD) with 95% confidence intervals (CI) was calculated when data units were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
1
14
0
1
Order By: Relevance
“…In the evaluation of vitamin D supplementation for HOMA-IR, which included four studies, vitamin D supplementation did not exert reduction in HOMA IR (WMD = 0.380, 95% CI: -0.162, 0.923; P = 0.169). 22 Comparing all the data available, the current systematic review and meta-analysis provide more reports that vitamin D supplementation improve insulin resistance in NAFLD patients, similar to meta-analysis by Guo et al Although similar meta-analysis had been conducted, the current meta-analysis provide updated literature with more RCTs involved, hence providing stronger evidence for the effect of vitamin D supplementation on insulin resistance.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the evaluation of vitamin D supplementation for HOMA-IR, which included four studies, vitamin D supplementation did not exert reduction in HOMA IR (WMD = 0.380, 95% CI: -0.162, 0.923; P = 0.169). 22 Comparing all the data available, the current systematic review and meta-analysis provide more reports that vitamin D supplementation improve insulin resistance in NAFLD patients, similar to meta-analysis by Guo et al Although similar meta-analysis had been conducted, the current meta-analysis provide updated literature with more RCTs involved, hence providing stronger evidence for the effect of vitamin D supplementation on insulin resistance.…”
Section: Discussionsupporting
confidence: 59%
“…20 Another meta-analysis study by Wei et al in 2020 also found that serum alanine aminotransferase and aspartate aminotransferase levels were not different between vitamin D supplementation and placebo groups. 22 The current systematic review and meta-analysis also objected to limitation. The heterogeneity of the current meta-analysis may affect the results obtained in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…However, vitamin D treatment has not consistently conferred expected therapeutic benefits. A new result of a meta-analysis indicated that vitamin D supplementation does not improve glucose metabolism parameters or lipid levels [ 138 ]. Moreover, plasma and hepatic ROS levels are decreased in the liver of VDR-deficiency mice compared to WT mice with acute hepatitis [ 139 ].…”
Section: Transcriptional Regulation Of Lipid Metabolism By Nrs In Nafldmentioning
confidence: 99%
“…Specifically, it has been shown that total testosterone is inversely related to NAFLD in men, and the previously increased use of testosterone replacement may be encouraged if more exploration studies could be warranted [ 142 , 143 ]. Another recent study implied that vitamin D supplementation has no effect in patients with NAFLD since there are no changes in lipid profile or liver enzymes; however, when combined with vitamin E, calcium, or omega-3 fatty-acid supplementation, potential benefits emerged in those patients [ 144 ]. Nevertheless, new therapeutic strategies may be required to reduce the impact of NAFLD on modern society.…”
Section: Conclusion and Perspectivementioning
confidence: 99%